Fiber rich food suppressed airway inflammation, GATA3 + Th2 cells, and FcεRIα+ eosinophils in asthma - Schenzel, Alicia; Geiger, Adriana; Nendel, Elvedina; Yang, Zuqin; Krammer, Susanne; Leberle, Anna; Brunst, Ann-Kathrin; Trump, Sonja; Mittler, Susanne; Rauh, Manfred; Geppert, Carol I.; Tausche, Patrick; et al. (Frontiers in Nutrition, 2024)
Objective: In this work, the role of high fiber diet on the development of allergic asthma at baseline 48 and after exacerbation of disease induced by respiratory viruses was investigated. Results: In this study, a decrease of the SCFA 3-Hydroxybutyric acid in serum of asthmatic children after symptomatic episodes at convalescent visit as compared to asthmatic and control children at baseline visit was observed. In experimental asthma, in mice fed with high fiber diet, a reduced lung GATA3+Th2 type mediated inflammation, mucus production and collagen deposition and expression of Fc epsilon receptor Ia (FcεRIa) in Eosinophils was observed. By contrast, the CD8+ memory effector T cells were induced in the lung of asthmatic mice fed with high fiber diet. Then, total lung cells from these asthmatic mice fed with either standard food or with fiber rich food were infected with RVex vivo. Here, RV1b mRNA was found significantly reduced in the lung cells derived from fiber rich food fed mice as compared to those derived from standard food fed asthmatic mice. Looking for the mechanism, an increase in CD8+ T cells in RV infected spleen cells derived from fiber rich fed asthmatic mice, was observed. Conclusion: Convalescent preschool asthmatic children after a symptomatic episode have less serum ß-Hydroxybutyric acid as compared to control and asthmatic children at baseline visit. Fiber rich diet associated with anti-inflammatory effects as well as anti-allergic effects by decreasing Type 2 and IgE mediated immune responses and inducing CD8+ memory effector T cells in a murine model of allergic asthma. Finally, ex vivo infection with Rhinovirus (RV) of total lung cells from asthmatic mice fed with fiber rich food led to a decreased RV load as compared to mice fed with standard food. Moreover, spleen cells derived from asthmatic mice fed with fiber rich food induced CD8+ T cells after ex vivo infection with RV. Clinical implications: Dietary interventions with increased content in natural fibers like pectins, would ameliorate asthma exacerbations. Moreover, respiratory infection in asthma downregulated SCFA in the gut contributing to asthma exacerbations.